Dealing With Human Rights in International Organizations. Issue 1 (2nd January 2016) - Hug, Simon
Abstract : Over time human rights have gained prominence in international organizations. At the same time, dealing with them has proved difficult and contentious. The present article focuses on the way in which the United Nations have addressed human rights issues, especially through the Commission on Human Rights (UNCHR) and its successor the Human Rights Council (UNHRC). Drawing on data on resolutions debated and (largely) adopted in these two bodies in the last 17 years, I offer a comparison of the voting record in these two periods. By analyzing in detail in a comparative fashion the votes in these two bodies, the article shows that despite the high hopes, the UNHRC faces some of the same challenges as its predecessor. More specifcally, I find that the conflict lines have largely remained the same in these two bodies, and the degree of polarization has slightly increased in the new UNHRC.